Pure Primary Ovarian Squamous Cell Carcinoma Perforating the Rectum - Kazuya Mimura; Aiko Okada; Naotsugu Haraguchi; Kenjiro Sawada; Takuji Tomimatsu; Tadashi Kimura (Case Reports in Obstetrics and Gynecology)
Rectal perforation is uncommon in ovarian cancer, even in advanced stages. Pure primary ovarian squamous cell carcinoma is a very rare subtype of ovarian cancer and has not been reported to cause rectal perforation. A 50-year-old woman presented with rectal bleeding. Rectosigmoidoscopy suggested perforation of a pelvic tumor into the rectum. Abdominopelvic magnetic resonance imaging revealed a 9 cm heterogeneous mass in the pouch of Douglas. We performed complete cytoreduction, including an en-bloc resection of the tumor and rectosigmoid colon. Histopathology showed squamous cell carcinoma of the left ovary penetrating the rectal wall. A common symptom of rectal bleeding was caused by a very rare entity of ovarian cancer penetrating the rectal wall, but thorough evaluation led to its accurate diagnosis and appropriate treatment.